Abdominal pain and symptoms before and after Roux-en-Y gastric bypass. Issue 3 (4th March 2019) - Chahal-Kummen, M; Blom-Høgestøl, I K; Eribe, I; Klungsøyr, O; Kristinsson, J; Mala, T
Abstract: Background: Despite increased emphasis on patient-reported outcomes, few studies have focused on abdominal pain symptoms before and after Roux-en-Y gastric bypass (RYGB). The aim of this study was to quantify chronic abdominal pain (CAP) in relation to RYGB. Methods: Patients with morbid obesity planned for RYGB were invited to participate at a tertiary referral centre from February 2014 to June 2015. Participants completed a series of seven questionnaires before and 2 years after RYGB. CAP was defined as patient-reported presence of long-term or recurrent abdominal pain lasting for more than 3 months. Results: A total of 236 patients were included, of whom 209 (88·6 per cent) attended follow-up. CAP was reported by 28 patients (11·9 per cent) at baseline and 60 (28·7 per cent) at follow-up ( P < 0·001). Gastrointestinal Symptom Rating Scale (GSRS) scores (except reflux scores) and symptoms of anxiety increased from baseline to follow-up. Most quality of life (QoL) scores (except role emotional, mental health and mental component scores) also increased. At follow-up, patients with CAP had higher GSRS scores than those without CAP, with large effect sizes for abdominal pain and indigestion syndrome scores. Patients with CAP had more symptoms of anxiety, higher levels of catastrophizing and lower QoL scores. Baseline CAP seemed to predict CAP at follow-up. Conclusion: The prevalence of CAP is higher 2 years after RYGB compared with baseline values. Graphical Abstract: Chronic abdominal pain (CAP) was seen in 28 of 236 patients (11·9 per cent) before and in 60 of 209 patients (28·7 per cent) 2 years after Roux-en-Y gastric bypass (RYGB). Patients with CAP at follow-up had more gastrointestinal symptoms, anxiety and reduced quality of life, compared with patients who did not have CAP. Increased attention should be given to CAP. In preoperative consultations, patients should be informed about CAP as a potential outcome after RYGB. Deserves greater attention